Relation between habitat characteristics and abundance, diet and condition of 0-group cod in two northern Norwegian fjords - Heggland, Kristin Nymark (Universitetet i Tromsø, 2013)
There is a correlation between the vegetation coverage and the abundance of 0-group cod. The highest abundance was found between 50 – 70 %, which is consistent with previous studied and imply that there is a nonlinear relationship between vegetation coverage and abundance of 0-group cod. There was found a difference in diet between the three habitats, with the intertidal zones of Balsfjord and Porsangerfjord having a diet significantly higher diversity than the 0-group cod in the pelagic zone of Porsangerfjord. The diet of the intertidal zones of Balsfjord and Porsangerfjord had a fairly similar composition, with a mixture of pelagic and bottom dwelling prey categories, whereas the diet of the cod in the pelagic zone had a dominance of pelagic prey categories. Body condition, expressed as weight at length, was different between the habitats. The 0-group cod from the intertidal zone form Porsangerfjord had significantly lower weight at length than that of the intertidal zone in Balsfjord and the pelagic in Porsangerfjord.